Identification and selection of local carrot seeds (Daucus carota L) for seed sources - Winda Purnama Sari; Meisilva Erona Sitepu; Irawati Chaniago (JERAMI : Indonesian Journal of Crop Science, 2021)
Carrot (Daucus carota) is one of the most important root vegetables in Indonesia contains high levels of sugars, rich in β-carotene (pre-vitamin A), ethylene, and high levels of proteins. Carrot was reported as a medicinal plant in the gardens and an essensial part of the food coloring industry. In fact the seeds of carrot contain estrogen, and in some cultures are used as an effective method of contraception. Carrot have been promoted as a future ingredient in biofuels, the carrot seed oil has proved to be an excellent lubricant in industrial applications, appears in multitude of skin and hair care products and produced luteolin. Carrot grows vegetatively in the first season and produced seed in the second. The yield and quality of carrot grown is determined by the seed production technique which can flourish carrot seed production as well as to compensate high cost of carrot seed. The use of local varieties of carrot as seed source increase productivity through higt adaptability. The aim of research is to obtain the best possible tuber characteristic as a qualified seed source. Research was conducted by the exploration method of carrot tuber in Lembang Jaya area and study the morphological characters. The exploration result obtained 8 carrot tuber locations. The carrot tuber with a chantenay type had the best growth and yields of the seeds to develop.